Faktor yang Berhubungan dengan Stres Kerja Perawat IGD Lantai I RSUP Prof. Dr. Kandou Manado - Melany Kumayas; Abdul Rohim Tualeka; Enjelita Karujan (FORIKES, 2023)
Nurse is a profession that is at high risk of experiencing work stress because it is responsible for the safety of human life. This study aimed to analyze factors related to work stress of nurses in the Emergency Room Floor I of Prof. Hospital. Dr. Kandou Manado. The research design was cross-sectional. The sample size in this study was 57 nurses who were selected by simple random sampling technique. Data was collected by filling out a questionnaire, then analyzed using the Spearman correlation test. The results of this study indicated that there was a relationship between mental demands (p value = 0.029), workload and responsibility (p value = 0.000) and the work stress of nurses. However, there was no relationship between social support (p value = 0.416) and the work stress of nurses. The conclusion in this study was that factors related to work stress on nurses in the Emergency Room, Floor 1, Prof. Hospital. Dr. Kandou Manado was a mental demand, workload and responsibility.Keywords: work stress; mental demands; workload and responsibility ABSTRAK Perawat adalah profesi yang berisiko tinggi terkena stres kerja karena bertanggung jawab terhadap keselamatan nyawa manusia. Penelitian ini bertujuan untuk menganalisis faktor yang berhubungan dengan stress kerja perawat di Instalasi Gawat Darurat Lantai I RSUP Prof. Dr. Kandou Manado. Rancangan penelitian ini adalah cross-sectional. Besar sampel dalam penelitian adalah 57 perawat yang dipilih dengan teknik simple random sampling. Data dikumpulkan melalui pengisian kuesioner, lalu dianalisis menggunakan uji korelasi Spearman. Hasil penelitian ini menunjukkan bahwa terdapat hubungan antara tuntutan mental (nilai p = 0,029), beban kerja dan tanggung jawab (nilai p = 0,000) dengan stres kerja perawat. Namun tidak terdapat hubungan antara dukungan sosial (nilai p = 0,416) dengan stress kerja perawat. Kesimpulan dalam penelitian ini yaitu faktor yang berhubungan dengan stres kerja pada perawat Instalasi Gawat Darutat Lantai 1 RSUP Prof. Dr. Kandou Manado adalah tuntuan mental, beban kerja dan tanggung jawab.Kata kunci: stres kerja; tuntutan mental; beban kerja dan tanggung jawab